The Transformation of Zakat in Indonesia: Integrating Religious Obligation and State Responsibility in Pursuit of Economic Justice - Restia Gustiana; Najikha Akhyati; Maria Ulfa (Universitas Muhammadiyah Makassar, 2025)
This research aims to analyze the regulation of zakat in the Indonesian legal system as well as evaluate its implementation as an instrument of community economic justice, by examining the balance between religious obligations and the role of the state in the management of zakat. The research uses normative-empirical approach with descriptive-qualitative analysis method. Primary data is obtained from the study of Law No. 23/2011 on Zakat Management, its derivative regulations, and court decisions related to zakat disputes. Secondary data include reports of the National Amil Zakat Agency (BAZNAS), scientific articles, and previous research on the effectiveness of zakat in economic development. Data collection is done through document study and literature review. Data analysis uses content analysis of zakat regulations and policies to identify gaps between theory and practice. The results show that zakat regulation in Indonesia has provided strong legal legitimacy, but its implementation still faces obstacles such as institutional fragmentation between BAZNAS and LAZ. Religiously, there is still low compliance of Muslim society to give zakat. In addition, Zakat has the potential to be an effective economic redistribution tool, but its distribution has not been optimal in reducing social inequality. The role of the state in supervision and standardization of zakat management needs to be strengthened to ensure transparency and accountability. This study concludes that the integration of religious obligation and state responsibility in zakat regulation has not fully achieved the goal of economic justice, so more progressive policy reforms are needed.